Gut microbiota and blood biomarkers in IBD-Related arthritis: insights from mendelian randomization - Wei Yang; Miao Cui; Peng Yang; Chenlin Liu; Xiuzhen Han; Wenyi Yao; Zhenhua Li (Scientific Reports)
Abstract With the ongoing rise in the incidence of inflammatory bowel disease (IBD), its extraintestinal manifestations have garnered significant attention. IBD-related arthritis is notable for its insidious onset and unpredictability, presenting considerable challenges for clinical diagnosis and management. Factors such as gut microbiota, plasma proteins, inflammatory proteins, and biomarkers found in blood and urine may be closely associated with IBD-related arthritis. However, the mechanisms by which these factors influence this condition remain poorly understood and require urgent investigation. We employed the method of linkage disequilibrium and the two-sample Mendelian randomization (MR) approach, utilizing single nucleotide polymorphisms (SNPs) identified from large-scale genome-wide association studies as instrumental variables. In this scientifically rigorous manner, we explored the potential causal relationship between gut microbiota, plasma proteins, inflammatory proteins, and blood and urine biomarkers in relation to arthritis resulting from inflammatory bowel disease (IBD). This method aids in elucidating the potential roles of these biomarkers in the development of arthritis following IBD, while minimizing the confounding factors and reverse causality commonly encountered in observational studies. To further verify and strengthen our findings, we conducted subsequent sensitivity analyses. These analyses will evaluate the strength of the association between SNPs and the studied biomarkers, as well as post-IBD arthritis, while accounting for variations in SNP distribution among populations and other potential genetic influencing factors. Through these rigorous analytical steps, our objective is to enhance the robustness and credibility of the research findings and provide more reliable scientific evidence regarding the pathogenesis of post-IBD arthritis. MR analysis provides evidence for the association between genetically predicted gut microbiota, plasma proteins, inflammatory proteins, and blood and urine biomarkers with the risk of IBD-related arthritis. This analysis investigates the characteristics of the associations between specific gut microbiota, plasma proteins, inflammatory proteins, and blood and urine biomarkers in relation to IBD-related arthritis. Among the plasma proteins, pterin-4-alpha-carbinolamine dehydratase, aldo-keto reductase family 1 member C4, cathepsin L2, angiostatin, hepatocyte growth factor-like protein, hepatitis A virus cellular receptor 2, protein O-linked mannose beta-1,4-N-acetylglucosaminyltransferase 2, epididymal-specific alpha-mannosidase, and platelet-derived growth factor receptor-like protein are associated with Crohn’s disease-related arthritis. In contrast, agrin, methylenetetrahydrofolate synthetase domain-containing protein, neurotrophin-3 (NT-3) growth factor receptor, and neuropilin-1 are associated with ulcerative colitis-related arthritis. Furthermore, regarding gut bacterial pathway abundance, adenosylcobalamin, N-acetylglucosamine, N-acetylmannosamine, and N-acetylneuraminic acid degradation, as well as glycolysis metabolism and degradation pathways, are associated with Crohn’s disease-related arthritis. Meanwhile, gut bacterial pathway abundance (pentose phosphate pathway) and gut microbiota abundance (Bacteroidetes, Bacteroidia, Bacteroidales, Porphyromonadaceae, Faecalibacterium, Eubacterium eligens) are linked to ulcerative colitis-related arthritis. Notably, we did not identify any connections between inflammatory protein factors, blood and urine biomarkers, and IBD-related arthritis. Lastly, in the reverse MR study, the insufficient number of SNPs available for analysis precluded the detection of a reverse causal relationship. This study employs the MR method to elucidate the potential causal relationships among gut microbiota, plasma proteins, inflammatory proteins, and blood and urine biomarkers in relation to the occurrence and progression of IBD-related arthritis. This research offers a novel perspective for a deeper understanding of the pathogenesis of IBD-related arthritis and highlights future directions for the diagnosis and treatment strategies of this condition.